A Concurrent tuberculosis and paratuberculosis in a beetal goat (Indian Journal of Veterinary Pathology, 2025)
A two year old female beetal goat was presented with history of diarrhea and progressive weight loss. On hematology, severe anaemia (Hb = 2.9g/dl) and neutrophilic leukocytosis were observed. Ante-mortem fecal examination revealed positive for acid fast bacilli. The animal succumbed to death. On postmortem examination, the carcass showed emaciation and diarrhoeic feces found to be adhered in the perineal and tail region. Grossly, lung revealed edema, congestion along with hard caseated nodules in focal areas and trachea was frothy. Intestine revealed catarrhal enteritis, and also showed thickening of the intestinal mucosa at the caeco-iliac junction. Mesenteric lymph nodes were swollen and caeseated. Impression smear from intestine and lung were positive for acid fast bacilli. Histopathologically lung exhibited focal to multifocal necrotizing lesion at the centre and surrounded by epitheloid cells and Langhan’s giant cell, indicating typical TB granuloma. Further, immunohistochemistry and PCR using specific primers for Mycobacterium tuberculosis complex and Mycobacterium avium subsp paratuberculosis confirmed the presence of tuberculosis and paratuberculosis respectively.